Master storyteller's challenging vision - Josephine Latu (Asia Pacific Network, 2009)
In Search Of The Friendly Islands, his sophomore publication, is sure to make wakes— and not only with the governing authorities. It is a jolting dose of realism for any Tongan. The title address Moala's scepticism with the myth of a perpetually serene and culturally idolised 'Friendly Islands'.